BUILDING 21ST CENTURY SKILLS IN THE DIGITAL ERA: THE ROLE OF THE PJBL MODEL ON THE COLLABORATION OF GRADE 5 STUDENTS - Warmiati; Rusijono; Fajar Arianto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The digital era requires students to master 21st century skills, where collaboration is one of the crucial competencies that must be formed from an early age. However, challenges in the field show that passive interaction and individualism still dominate the conventional learning process at the elementary school level. This study aims to analyze the role of the Project-Based Learning (PjBL) learning model in improving the collaboration skills of grade 5 elementary school students. The research method used is a quasi-experimental type of Nonequivalent Control Group Design with data collection techniques through observation and questionnaires. PjBL was chosen because of its characteristics that are based on group investigation and real problem solving that are relevant to today's digital ecosystem. The results of the study showed that the implementation of PjBL significantly increased the indicators of student collaboration including: (1) Contribution in group discussions to 88.45%, (2) Time management to 85.75%, (3) Problem solving to 86.50%, (4) Working with friends 86.34%, (5) Investigation techniques 87.80%. The integration of digital devices in the PjBL project also accelerates access to information and coordination between students. The conclusion of this study emphasizes that PjBL is not just an instructional model, but a strategy to transform traditional classrooms into a collaborative and adaptive learning environment to the demands of the times.